Danshen (Salvia miltiorrhiza) water extract shows potential neuroprotective effects in Caenorhabditis elegans. (10th February 2021) - Yuen, Chee Wah; Murugaiyah, Vikneswaran; Najimudin, Nazalan; Azzam, Ghows
Abstract: Ethnopharmacological relevance: Danshen, is a traditional Chinese medicine obtained from the dried root and rhizome of Salvia miltiorrhiza Bunge. It is known to be used for neurological disorder including for Alzheimer's disease (AD). This study uncovers the effect of Danshen water extract on the Alzheimer's disease model of C.elegans . Material and methods: The composition of Danshen water extract was determined using (High Performance Liquid Chromatography (HPLC). Then Thioflavin T assay was used to determined if Danshen water extract could prevent the aggregation of amyloid-β peptide (Aβ). Alzheimer's disease C.elegans model was used to determine the effect of Danshen water extract. Finally, the reactive oxygen species (ROS) was determined using the 2, 7-dichlorofuorescein diacetate method. Results: In this study, we found that standardized Danshen water extract that contains danshensu (1.26%), salvianolic acid A (0.35%) and salvianolic acid B (2.21%) are able to bind directly to Aβ and prevents it from aggregating. The IC50 for the inhibition of Aβ aggregation by Danshen water extract was 0.5 mg/ml. In the AD model of C.elegans, Danshen water extract managed to alleviates the paralysis phenotype. Furthermore, the administration of Danshen water extract displayed antioxidant properties toward the Aβ-induced oxidative stress. Conclusions: AD is a widespread neurodegenerative disease attributed to the accumulation of extracellular plaques comprising Aβ. Danshen water extract could significantly reduce the progress of paralysis in the AD model of C. elegans, showing promising results with its antioxidant properties. It can be concluded that Danshen water extract could potentially serve as a therapeutic for AD. Graphical abstract: Image 1